Gender, space and entrepreneurship: a case study of Felda women entrepreneurs in Johor, Malaysia - Selamat, Nor Hafizah; Hayrol Aziz, Farah Syazwani; Anuar, Adzam; Azmi, Zaireeni; Endut, Noraida (2015)

(untitled)
Since the establishment of FELDA (Federal Land Development Authority) in 1956, a series of entrepreneurship programs and incentive have been introduced through its Entrepreneur Development Department with the objective to improve and strengthen the knowledge and skills of entrepreneurs and potential entrepreneurs in FELDA. It is estimated that there are 1.97 million women in FELDA throughout Malaysia and 4,725 of them are women’s entrepreneurs, involving in various business sectors. Several studies have been done on women entrepreneurship in FELDA, however, knowledge about the places from which women entrepreneurs operate and its relations to gender roles is still under research. The ability of entrepreneurs to establish a productive business is very much determined by factors such as who they are, where they are located, and how they interact within space. By using gender analyses, this paper will be examining women entrepreneurs’ lived experiences, how entrepreneurship space is created and how women’s use of space as a survival strategy through entrepreneurship. Using in-depth interviews and observation, 16 women entrepreneurs were selected in FELDA Ulu Tebrau to share their entrepreneurship activities and experiences. The preliminary finding shows that most women entrepreneurs locate their businesses close to home either inside the house, in the house compound or just beside the roadside in front of their houses as they are not being relieved from the household work. Gender roles are likely inhibiting women entrepreneurs’ spatial range and therefore their business location. The existing government policies may not capture all of the impediments to women’s business growth. Therefore, more attention is needed to understand and address the gendered role of place and space to ensure that women entrepreneurs have equal opportunity to expand their business’s growth.